IN-HOSPITAL BLOOD PRESSURE VARIABILITY AS A PREDICTOR OF CARDIOVASCULAR OUTCOMES IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION: ONE-YEAR FOLLOW-UP STUDY. (April 2021) - Konstantinou, K.; Tsioufis, K.; Koumeli, A.; Dri, E.; Kalos, T.; Kouremeti, M.; Vogiatzakis, N.; Magkas, N.; Mantzouranis, M.; Kolokathis, K.; Leontsinis, I.; Tolis, E.; et al.
Abstract : Objective: The impact of blood pressure variability (BPV) on cardiac function has been examined through the prism of congestive heart failure and hypertension, but not in the setting of an acute coronary syndrome (ACS). The aim of this study is to determine the association between in-hospital short-term BPV and long-term cardiovascular morbidityin patients with myocardial infarction (MI). Design and method: A total population of 260 MI patients [82.2% male; mean age: 63.8 years;71.3% hypertensives, 29.5% with diabetes mellitus (DM), 48.1% with STEMI]underwent 24-h ambulatory BP measurement during hospitalization.At one year a follow-up visit was scheduled in order to assess major cardiovascular outcomes. These included hospitalization for heart failure (HF), stroke, ACS, life threatening arrythmias. BPV was assessed using the average real variability (ARV) of systolic and diastolic BP. Results: Univariate analysis demonstrated that both ARV SBP and ARV DBP were predictors of overall hospitalizations for cardiovascular events in the entire population[(HR = 1.045; 95% CI: 0.542–1.547; P = 0.001) and (HR = 0.991; 95% CI: 0.536–1.446; P < 0.001)] but also in the STEMI [(HR = 1.138; 95% CI: 0.487–1.789; P = 0.001) and (HR = 0.947; 95% CI: 0.318–1.576; P = 0.003) respectively] and NSTEMI [(HR = 1.035; 95% CI: 0.278–1.793; P = 0.008) and (HR = 1.061; 95% CI: 0.394–1.728; P = 0.002) respectively] groups separately. Regarding hospitalization for HF, both ARV SBP and ARV DBP emerged as predictors in the entire population [(HR = 1.027; 95% CI: 0.093–1.960; P = 0.031) and (HR = 1.798; 95% CI: 0.972–2.624; P < 0.001) respectively] and in STEMI patients [(HR = 1.664; 95% CI: 0.517–2.811; P = 0.005) and (HR = 2.408; 95% CI: 1.360–3.455; P < 0.001) respectively], but not in the NSTEMI group.Independency of all the above predictors was confirmed in multivariate models including gender, age, hypertension, DM, smoking, low density lipoprotein (LDL-C) and GFR. Conclusions: In the setting of MI, in-hospital ARV was associated with increasedcardiovascular morbidityduring one-year follow-up. These findings could suggest a closer monitoring of patients suffering a MI and exhibiting increased BPV during hospitalization.